Magnetic wire active microrheology of human respiratory mucus. Issue 32 (3rd August 2021) - Radiom, Milad; Hénault, Romain; Mani, Salma; Iankovski, Aline Grein; Norel, Xavier; Berret, Jean-François
Abstract : Micrometer-sized magnetic wires are used to study the mechanical properties of human mucus collected after surgery. Our work shows that mucus has the property of a high viscosity gel characterized by large spatial viscoelastic heterogeneities. Abstract : Mucus is a viscoelastic gel secreted by the pulmonary epithelium in the tracheobronchial region of the lungs. The coordinated beating of cilia moves mucus upwards towards the pharynx, removing inhaled pathogens and particles from the airways. The efficacy of this clearance mechanism depends primarily on the rheological properties of mucus. Here we use magnetic wire based microrheology to study the viscoelastic properties of human mucus collected from human bronchus tubes. The response of wires between 5 and 80 μm in length to a rotating magnetic field is monitored by optical time-lapse microscopy and analyzed using constitutive equations of rheology, including those of Maxwell and Kelvin-Voigt. The static shear viscosity and elastic modulus can be inferred from low frequency (3 × 10 −3 –30 rad s −1 ) measurements, leading to the evaluation of the mucin network relaxation time. This relaxation time is found to be widely distributed, from one to several hundred seconds. Mucus is identified as a viscoelastic liquid with an elastic modulus of 2.5 ± 0.5 Pa and a static viscosity of 100 ± 40 Pa s. Our work shows that beyond the established spatial variations in rheological properties due to microcavities, mucus exhibits secondary inhomogeneities associated with the relaxation time of the mucin network that may be important for its flow properties.